2021
DOI: 10.3390/ijerph182111431
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review Investigating Relationships between Depression, Anxiety, and the PrEP Care Continuum in the United States

Abstract: Men who have sex with men and transgender women in the United States are at increased risk for HIV and may benefit from pre-exposure prophylaxis (PrEP), a once-a-day pill to prevent HIV. Due to stigma and discrimination, sexual and gender minority (SGM) populations are also at risk for depression and anxiety. This scoping review sought to identify literature addressing relationships between the PrEP care continuum, depression, and anxiety among SGM individuals and others at high risk for HIV. We conducted a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 89 publications
3
7
0
Order By: Relevance
“…addition, the significant association between those who were living with HIV and ART non-adherent experiencing psychological distress is consistent with previous documentation of mental health challenges as a barrier to ART adherence. 20 Our findings of a lack of association between PrEP adherence and psychological distress is not, however, consistent with prior studies showing an association between increased mental health challenges and adherence, although the prior studies measured depression and anxiety which limits direct comparison to these studies. 17,18,19,20,21 Many approaches have aimed to address poor mental health as a barrier to medication adherence.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…addition, the significant association between those who were living with HIV and ART non-adherent experiencing psychological distress is consistent with previous documentation of mental health challenges as a barrier to ART adherence. 20 Our findings of a lack of association between PrEP adherence and psychological distress is not, however, consistent with prior studies showing an association between increased mental health challenges and adherence, although the prior studies measured depression and anxiety which limits direct comparison to these studies. 17,18,19,20,21 Many approaches have aimed to address poor mental health as a barrier to medication adherence.…”
Section: Discussionsupporting
confidence: 64%
“…20 Our findings of a lack of association between PrEP adherence and psychological distress is not, however, consistent with prior studies showing an association between increased mental health challenges and adherence, although the prior studies measured depression and anxiety which limits direct comparison to these studies. 17,18,19,20,21…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have identified mental health concerns such as depression and anxiety as barriers to PrEP uptake and adherence for transgender women [ 34 , 35 ]. In our study, more than 30% of survey respondents reported receiving diagnoses of depression and anxiety, while 9% and 4% noted diagnoses of post-traumatic stress disorder (PTSD) and bipolar disorder, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to physiological, socio-psychological, structural, and other factors, the risk of HIV infection in MSM is more than ten times higher than that of the general population ( Chen and Ma, 2018 ), and it is also the most rapid population of HIV infection in China at present. Several studies have pointed out that high-risk behavior and HIV infection are related to psychological problems, such as anxiety and depression ( Hanrahan et al, 2011 ; Pappin et al, 2012 ; Hill et al, 2018 ; Rogers et al, 2018 ; Miller et al, 2021 ). At present, most HIV prevention strategies for MSM are behavioral interventions, such as strengthening the condom use, promoting pre-exposure prophylaxis (PrEP), encouraging regular HIV testing, and consultation, which ignore the effect of psychological intervention in HIV prevention and control.…”
Section: Introductionmentioning
confidence: 99%